1999
DOI: 10.1017/s1355617799566083
|View full text |Cite
|
Sign up to set email alerts
|

MRI extrahippocampal volumes and visual memory: Correlations independent of MRI hippocampal volumes in temporal lobe epilepsy patients

Abstract: Limbic system atrophy and memory dysfunction are common in patients with temporal lobe epilepsy (TLE). However, the relationship between extrahippocampal limbic structures and memory functioning within TLE has received little attention. The present study examined associations of MRI volumetric measurements of the mammillary body, fornix, amygdala, and hippocampus to measures of episodic verbal and visual memory. The Logical Memory and Visual Reproduction subtests from the Wechsler Memory Scale were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 52 publications
6
32
1
Order By: Relevance
“…Initial studies focused exclusively on hippocampal volumes and their relationship to memory dysfunction in temporal lobe epilepsy (TLE) ((1-3), for a review, see (4)). These studies demonstrated a consistent relationship between reductions in left hippocampal volume, or hippocampal asymmetries, and impairments in verbal learning and memory, in TLE patients who were left-hemisphere dominant for language (1,2,(5)(6)(7)(8)(9). More importantly, these studies established that patients without left hippocampal volume loss were at greatest risk for postoperative memory decline (7).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 66%
See 2 more Smart Citations
“…Initial studies focused exclusively on hippocampal volumes and their relationship to memory dysfunction in temporal lobe epilepsy (TLE) ((1-3), for a review, see (4)). These studies demonstrated a consistent relationship between reductions in left hippocampal volume, or hippocampal asymmetries, and impairments in verbal learning and memory, in TLE patients who were left-hemisphere dominant for language (1,2,(5)(6)(7)(8)(9). More importantly, these studies established that patients without left hippocampal volume loss were at greatest risk for postoperative memory decline (7).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 66%
“…The association between right hippocampal volumes and nonverbal learning and memory is tenuous, but has been reported in a few studies (7,10,11). In addition, there are data to support the role of other medial temporal lobe structures in verbal and visual memory, including the amygdala (8,12), mammillary bodies (8), and perirhinal cortex (9,13). In fact, there is some evidence that right amygdala volume is a stronger predictor of visual memory than right hippocampal volume (8,12).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present study used a 1.0-mm-volume scan for comparison purposes, previous MR imaging studies of the mammillary bodies have used a variety of section thicknesses (1.0 mm, 31 1.1 mm, 28 1.5 mm, 29,30,32, and 3.0 mm 26,27 ). Other differences included the use of a 3T imaging system because previous MR imagingϪbased measurements of mammillary body volume have used 1.5T systems.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32] An additional MR imaging sequence was used to acquire intracranial volume data for normalizing the data for differences in head size across patients and controls. This sequence was a T2-weighted intracranial volume scan; parameters were TR, 3000 ms; TE, 102 ms; FA, 150°; 3-mm section thickness; 10-mm section gap; acquisition time, 2 minutes.…”
Section: Image Acquisitionmentioning
confidence: 99%